Collaborative workflow management using service oriented approach - Pudhota, Leo; Chang, Elizabeth (2005)
Collaborative workflow systems in large logistics companies require a well integrated information systems infrastructure and a strong communication network to meet major new challenges and opportunities. Agile infrastructure, enabled by integration, can have substantial impact on the overall success of a business, these IT integration requirements are expanding considerably with the advent of ebusiness; utilizing B2B (Business to Business) web services and P2P (Partner to Partner) e-commerce. This paper deals with change management of collaborative workflow in such consortia and proposes integration architecture for synchronization of these changes through the process of service modules integration where by existing workflow systems are adapted to the changes. This paper will describe conceptual framework and implementation strategy resulting in new collaborative workflow adaptation.